Modulation of the Binding of Matrix Gla Protein (MGP) to Bone Morphogenetic Protein-2 (BMP-2) - Wallin, Reidar; Cain, Dean; Hutson, Susan M.; Sane, David C.; Loeser, Richard (Thrombosis and Haemostasis, 2000)
Matrix Gla protein (MGP) is an inhibitor of calcification of the arterial wall but the mechanism of inhibition has not been resolved. Since chondrogenesis has been identified in calcified arteries from MPG null mice, we hypothesized that locally produced MGP might inhibit calcification by neutralizing the known effect of bone morphogenetic proteins (BMPs) as promotors of chondrogenesis and bone formation. As the first step to test this hypothesis, we demonstrate that MGP is a binding protein for 125I-BMP-2. Optimal binding is dependent on metals which suggests that the metal binding Gla region in MGP is involved. MGP is shown to undergo a Ca++ induced conformational change despite the presence of the γ-carboxylase binding site being part of the mature protein sequence. The data propose that MGP matures earlier in the secretory pathway than other vitamin K-dependent proteins. Antibodies were used in an attempt to identify MGP in bovine serum. Conformational specific MGP antibodies were shown to also recognize the Gla region in prothrombin and factor X but did not identify MGP in serum. This finding is supported by electrophoresis data which demonstrate the absence of MGP among Ba-citrate absorbed vitamin K-dependent serum proteins. We conclude that MGP does not exist in normal bovine serum.
Keywords: Vitamin K; arterial calcification; vitamin K-dependent proteins